Interactive Animation Multimedia for Knowing the Words (CV+CV) for Student with Learning Disabilities - Aliyah Yahya; Mohd Mokhtar Tahar (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
This research studies the design and development of the teaching and learning module with the assistance of interactive animation multimedia computer. The objective of this research is to address the following research questions, which are to enhance the interest and motivation of the special education learners as well as to facilitate the learners in identifying (CV+CV) syllables. The process in developing the software follows the ADDIE Model, which includes the five phases, namely “Analysis”, “Design”, “Development”, “Implementation” and “Evaluation”. The selection of topic in (CV+CV) syllables identification was made in order to help the special education learners in their reading process. The research method uses the Mayer’s Multimedia Learning Theory, which is based on Sweller’s Cognitive Load Theory (Chandler and Sweller). The research data was collected through a qualitative method and research design is a case study. The respondents of this research involve four learners selected through a sampling, who were then divided into one groups; namely Group A . The instruments of the research consist of a pre-test, a post-test and a questionnaire. The research finding shows that there is a significant increase ( 60% ) in the post-test of Group A. The learning through Interactive Animation Multimedia does not only attract the learners’ interest and enhance their motivation in learning, but also indirectly allows these special education learners to read.Keywords: ADDIE Model, Interactive Multimedia, and students with learning difficulties.Kajian ini mengenai pembangunan modul pengajaran dan pembelajaran (P&P) yang berbantukan kepada penggunaan komputer multimedia animasi interaktif. Tujuan kajian ini ialah untuk menjawab beberapa persoalan kajian iaitu, untuk meningkatkan minat dan motivasi pelajar pendidikan khas dan untuk memudahkan pelajar mengenal suku kata (KV+KV). Proses membangunkan perisian ini adalah berdasarkan kepada Model ADDIE yang mempunyai lima fasa iaitu “Analysis”, “Design”, “Development”, “Implementation” dan “Evaluation”. Pemilihan tajuk mengenal suku kata (KV+KV) adalah untuk membantu pelajar-pelajar pendidikan khas dalam proses membaca. Proses kajian ini menggunakan Teori Pembelajaran Multimedia oleh Mayer, dan teori ini juga adalah berdasarkan kepada Teori Beban Kongnitif Sweller ( Chandler & Sweller ). Kajian ini menggunakan kaedah kualitatif dan reka bentuk kajian ialah kajian kes. Sampel dalam kajian ini ialah seramai 4 orang pelajar yang dipilih secara sampel bertujuan yang telah dibentuk dalam satu kumpulan iaitu Kumpulan A. Instrumen kajian yang digunakan ialah ujian pra, ujian pos dan soal selidik. Dapatan kajian telah mendapati bahawa terdapat peningkatan pencapaian dalam ujian pra dan ujian pos yang menggunakan kaedah multimedia bagi Kumpulan A iaitu sebanyak (60 %) . Pembelajaran yang menggunakan kaedah Multimedia Animasi Interaktif bukan sahaja dapat menarik minat dan memberi motivasi kepada pelajar, secara tidak langsung juga pelajar pendidikan khas ini dapat membaca.DOI: http://dx.doi.org/10.17977/um029v4i12017p001